2021
DOI: 10.1177/03331024211056286
|View full text |Cite
|
Sign up to set email alerts
|

Migrainous infarction of the eye: Two cases of monocular ischemic complications associated with retinal migraine

Abstract: Background Retinal migraine is defined by fully reversible monocular visual phenomena. We present two cases that were complicated by permanent monocular vision deficits. Cases A 57-year-old man with history of retinal migraine experienced persistent monocular vision loss after one stereotypical retinal migraine, progressing to finger-count vision over 4 days. He developed paracentral acute middle maculopathy that progressed to central retinal artery occlusion. A 27-year-old man with history of retinal migraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The headache is preceded by aura symptoms, usually visual disturbances, in a third of migraine sufferers (4). For many years, migraine has been thought to be associated with a variety of ophthalmic diseases, such as central retinal artery and vein occlusions, anterior and posterior ischemic optic neuropathy, and normal-tension glaucoma (5)(6)(7)(8). One study showed that 24% of patients with retinal arterial occlusions had a history of migraine (9).…”
Section: Introductionmentioning
confidence: 99%
“…The headache is preceded by aura symptoms, usually visual disturbances, in a third of migraine sufferers (4). For many years, migraine has been thought to be associated with a variety of ophthalmic diseases, such as central retinal artery and vein occlusions, anterior and posterior ischemic optic neuropathy, and normal-tension glaucoma (5)(6)(7)(8). One study showed that 24% of patients with retinal arterial occlusions had a history of migraine (9).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced perfusion in the retina during migraine attacks could play a role in pathological processes in the eye. It has been reported that migraine is associated with an increased risk of retinal artery occlusion, 84 and there have been a few case reports of retinal infarction associated with retinal migraine attacks 85,86 . However, in both clinical practice and in the literature, these are rare reports and there is no overwhelming evidence that migrainous infarction occurs commonly whether in the brain 87 or retina.…”
Section: Discussionmentioning
confidence: 99%
“…Migraineurs may have acute and chronic changes in ocular perfusion, and recurrent migraines can also cause permanent damage to the brain and retina [251,252]. It has been reported that migraine is closely associated with various neurovascular eye diseases such as retinal artery occlusion, ischemic optic neuropathy, and glaucoma [253][254][255].…”
Section: Migrainementioning
confidence: 99%